2005
DOI: 10.1242/jcs.02556
|View full text |Cite
|
Sign up to set email alerts
|

The human Rothmund-Thomson syndrome gene product, RECQL4, localizes to distinct nuclear foci that coincide with proteins involved in the maintenance of genome stability

Abstract: Rothmund-Thomson syndrome (RTS) is a human genetic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 45 publications
6
108
3
Order By: Relevance
“…40 Burks et al 42 have shown that RECQL4 has a nuclear targeting signal in the N-terminus (amino acids 363 -492), but localization studies of RECQL4 have shown both nuclear and cytoplasmic localization. 1,40,42,43 Additional localization studies in various human cells have shown that RECQL4 forms discrete nuclear foci and it colocalizes with promyelotic leukemia protein (PML) nuclear bodies as well as with regions of ssDNA. RECQL4 also forms a complex with Rad51 and colocalizes with it in human cells after the induction of DNA double-strand breaks.…”
Section: Introductionmentioning
confidence: 99%
“…40 Burks et al 42 have shown that RECQL4 has a nuclear targeting signal in the N-terminus (amino acids 363 -492), but localization studies of RECQL4 have shown both nuclear and cytoplasmic localization. 1,40,42,43 Additional localization studies in various human cells have shown that RECQL4 forms discrete nuclear foci and it colocalizes with promyelotic leukemia protein (PML) nuclear bodies as well as with regions of ssDNA. RECQL4 also forms a complex with Rad51 and colocalizes with it in human cells after the induction of DNA double-strand breaks.…”
Section: Introductionmentioning
confidence: 99%
“…The intricate networks of associated proteins (which regulate DNA replication initiation and genome stability 13,19,21 ) are possibly fine-tuned differentially at the cellular, tissue, organ and organism levels. This flexibility may provide room for the variable manifestation of RECQL4 related defects.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, RECQL4 foci coincide with those formed by pro-myelocytic leukemia (PML) bodies and RECQL4 forms a complex and co-localizes with Rad51 and regions of single-stranded DNA (ssDNA) upon induction of DNA double-strand breaks (DSBs). 21 PML body and Rad51 foci have been shown to regulate the response to, and repair of DSBs. 22,23 These observations suggest that RECQL4 plays a role in the repair of DSBs by homologous recombination.…”
Section: Recql4mentioning
confidence: 99%
See 1 more Smart Citation
“…The indirect immunofluorescence assay was performed as described previously (Jiao et al, 2004;Petkovic et al, 2005). Briefly, cells grown on glass slides were incubated with 0.5% Triton X-100 in PBS for 5 min, fixed with 2% paraformaldehyde in PBS (20 min at room temperature (RT)), and permeabilized with 0.5% Triton X-100 in PBS (20 min at RT).…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%